First psychiatric hospitalization: a perspective of the care based on the patient's experience (Research, Society and Development, 2020)
This work analyzes the patient’s first hospitalization in a specialized psychiatric hospital, their arrival, stay, and the care received during the hospitalization. Qualitative, descriptive and analytical research, with consultation of statistic, medical records and semi-structured interviews of these patients in their first hospitalization. Patients report an idle routine during hospitalization, passiveness, lack of knowledge regarding the received treatment, short duration of care received by professionals and low autonomy over the prescribed medication. The patients do not recognize workshops or similar activity as treatment. They highlight the nursing station as a place where they feel safe, and point out the use of the clinical beds as a favorable and reassuring place for the first hospitalization. We recommended that the first hospitalization is performed by a multidisciplinary team which acts in accordance with territorial services, in direct partnership with the Psychosocial Care Center (CAPS) for joint action in the face of new crises.